Determinants of Financial Distress and the Role of Firm Size the Variables are CR, DAR, to FD and FS as Moderation - Hamzah, Zeze Zakaria; Gursida, Hari; Indrayono, Yohanes (The Es Economics and Entrepreneurship, 2024)
The objective of this study is to determine the elements that account for the impact of financial ratios on financial difficulty. This will be achieved by treating firm size as a moderating variable that either enhances or diminishes the independent variable in connection to the dependent variable during the Covid-19 pandemic. The survey comprised a total of 263 companies. Observations were carried out consistent with the specified criteria, resulting in a total sample size of 40 companies. This study use regression as the data analysis technique. 1) Finding shows current ratio has adverse effect to financial distress. 2) The debt-to-asset ratio positively affects financial stability. 3) The significance of the current ratio on financial difficulty is reduced with the size of the firm. 4) The debt-to-asset ratio during financial crises is influenced by the size of the firm.